2013
DOI: 10.5812/numonthly.12485
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Hemodialysis Patients: An Iranian Multi-Center Study

Abstract: BackgroundThe effectiveness of health care and health policy developments are often determined by health-related quality of life (HRQOL) assessment.ObjectivesThe objective of this study was to explore the potential corresponding factors and traditional biomarkers of HRQOL in a large number of Iranian hemodialysis patients.Patients and MethodsA total of 6,930 chronic hemodialysis (HD) patients enrolled. KDCS-SF version 1.3 questionnaire was used to assess the health related quality of life (HRQOL). We pooled PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 39 publications
(63 reference statements)
3
31
1
3
Order By: Relevance
“…Numerous studies have reported that HRQL is significantly affected in patients with CKD (Soni et al ; Untas et al ; Avramovic & Stefanovic ; Pagels et al ; Rostami et al ). On comparing the results obtained in our patients with those for a healthy reference population, according to the Spanish version of the SF‐36 questionnaire, we find that our scores were lower for all the general dimensions of the KDQOL‐SF, with a difference of the means ranging from 52.53 for the physical role to 4.09 for social support.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that HRQL is significantly affected in patients with CKD (Soni et al ; Untas et al ; Avramovic & Stefanovic ; Pagels et al ; Rostami et al ). On comparing the results obtained in our patients with those for a healthy reference population, according to the Spanish version of the SF‐36 questionnaire, we find that our scores were lower for all the general dimensions of the KDQOL‐SF, with a difference of the means ranging from 52.53 for the physical role to 4.09 for social support.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, females had poor self-reported health-related quality of life (HRQoL), but better survival than men [1]. We have also found a lower quality of life (QoL) score in women among 6,930 HD patients [2].…”
Section: Dear Editormentioning
confidence: 87%
“…Physical and Mental component summary scores in Iranian HD patients were 40.79 and 47.79 respectively [2]. Moreover, these parameters were different in American HD patients (34.4-37.7 and 41.73-41.7 respectively) [3] and Netherlands HD patients (38.8 and 43.7 respectively) [4].…”
Section: Letter To Editormentioning
confidence: 95%
“…The different ethnic groups may be another reason. For example, the prevalence of endstage renal disease (ESRD) and some risk factors of chronic kidney disease (CKD) such as hypertension and diabetes are widely different among various ethnic groups [2]. Age of participants, sample size and level of education which are different among countries are other important confounding factors.…”
Section: Letter To Editormentioning
confidence: 99%
See 1 more Smart Citation